PENGARUH POLUTAN Pb TERHADAP PERTUMBUHAN DAN PERKEMBANGAN TANAMAN Lantana sellowiana dan Ixora chinensis - Siti Nurisjah; G. A. Wattimena; Endang Syamsudin; Lily Taslim (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1994)
An experiment on the effect of Pb pollutants on the growth and development of two widely used ornamental plants, i.e. Lantana sellowiana and Ixora chinensis, was conducted at the IPB Greenhouse, Baranangsiang, Bogor from mid September 1990 to the end of December 1990. The experiment aimed to determine the effect of concentration levels of Pb in the form of PbCl2 upon the growth and development of the two ornamental plants. The experiment consisted of two units, each of which was based on the complete randomized design. Treatments consisted of four concentration levels of PbCI2, i.e. 0, 250, 2500, and 25 000 ppm, applied to each unit with three replications. Observation during 12 weeks showed that treatments with 250 and 2500 ppm PbCl2 did not give significant damage to the growth and development of Lantana sellowiana. Concentration level of 25 000 ppm, however, interfered growth and development of this species six weeks after planting. On the other hand, the concentration levels used in this experiment had no toxic effect on the growth and development of Ixora chinensis.